A transformational theory of organizations - McSwain, Cynthia J.; White, Orion F. (1993)
"This paper describes the key concepts of a transformational theory of organizations. The authors argue that transformational theory, based largely on the theories of the Swiss psychologist, Carl Jung, provides a way of conceptualizing organizational process by clarifying and grounding a number of critical innovations of organizational practice. The authors characterize transformational theory's basic assumptions - the ontological commitment, the epistemological commitment, praxis, the theory of social relationships - and highlight the distinctive nature of these assumptions compared to more traditional organization theories"
Keywords: Organization